Macroscopic Observations of Catastrophic Gas Hydrate Growth during Pipeline Operating Conditions with or without a Kinetic Hydrate Inhibitor - Sundramoorthy, J.D. (American Chemical Society, 2015)
This paper presents the macroscopic observation of catastrophic gas hydrate growth during a shut-in, cold start-up and flowing conditions, simulating a natural gas transmission line operation. All experiments are conducted with a fixed simulated natural gas composition to form structure II gas hydrate with 11 K subcooling in the isochoric rocking cells. In order to simulate inhibited test systems, a formulated copolymer of vinylpyrolidone and vinylcaprolactam (PVP/PVCap) is included in some of the cells studied. Detailed macroscopic images and interpretation of pressure (P) and temperature (T) data are used to present our findings. It is found that production profiles such as different shut-in time and the mechanism of mass transfer of water from the bulk water phase to gas hydrate phase influence the gas hydrate growth in distinctive ways. Moreover, the capillary force in the gas hydrate structure may provide a greater driving force to promote gas hydrate growth than the diffusion rate of gases into the bulk water phase under shut-in and cold-start up conditions. Additionally, the number of critical nuclei formed during the initial stage of gas hydrate growth may influence the type of bulk gas hydrate present in the system at a later stage, i.e., finely dispersed hydrates or a slush type of gas hydrate. Â© 2015 American Chemical Society.